2012
DOI: 10.1111/j.1471-4159.2012.07719.x
|View full text |Cite
|
Sign up to set email alerts
|

GluA and GluN receptors regulate the surface density of GluN receptor subunits in cultured neocortical interneurons

Abstract: J. Neurochem. (2012) 121, 597–606. Abstract In cultured rat neocortical interneurons, we have studied the effect of long‐term application of NMDA or AMPA on the surface density of the NMDA (GluN) receptor subunits GluN1 and GluN2B. Stimulation of Ca2+‐permeable AMPA (GluA) receptors located on the interneurons decreased the response of GluN receptors. The reduction was caused by a decrease in the surface density of GluN1/GluN2B subunits. In contrast, stimulation of GluN receptors located on the interneurons en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Fig. 2 C-F, when specified, neurons were incubated with an antibody binding to GluN1 extracellular domain (MAB363, Millipore); we note that this antibody allows for live labeling of surface NMDARs (43,44) for 60 min in normal culture media (10 μg/mL). Neurons were then washed once in culture media then incubated for 30-60 min with a secondary antibody (10 μg/mL; GAM-AF647, Life Technologies); both incubations were carried out at 37°C in the incubator.…”
Section: Methodsmentioning
confidence: 99%
“…Fig. 2 C-F, when specified, neurons were incubated with an antibody binding to GluN1 extracellular domain (MAB363, Millipore); we note that this antibody allows for live labeling of surface NMDARs (43,44) for 60 min in normal culture media (10 μg/mL). Neurons were then washed once in culture media then incubated for 30-60 min with a secondary antibody (10 μg/mL; GAM-AF647, Life Technologies); both incubations were carried out at 37°C in the incubator.…”
Section: Methodsmentioning
confidence: 99%
“…The reduction in network bursts is due to changes in presynaptic activity which cause a pronounced decrease in glutamate release (Cohen and Segal 2009). It is tempting to hypothesize that the decrease in GluN receptor density observed in our experiments was caused by a lack of stimulation brought about by chronic application of NMDA (see the accompanying paper by D. K. Meyer et al 2012).…”
Section: Discussionmentioning
confidence: 83%
“…In this study, we found CMS-induced decrease in the intercommunicating molecules between neuron and microglia (Cx3cl1 / Cx3cr1 and CD200 / CD200R) in hippocampus of CMS-exposed mice was reversed by ASA VI treatment. Meanwhile, the PSD-95, CamKII α and CamKII β as well as decreased levels of phosphorylated GluA 2 in hippocampus of CMS-exposed mice, these are thought to be crucial for morphological maturation and synaptic development of hippocampal neurons [42][43][44][45][46][47], were partially reversed by asperosaponin VI via PPAR-γ-dependent pathway. These results reveal for the rst time the role of asperosaponin VI in maintaining normal communication between neurons and microglia as well as in repairing CMS-induced damage to synaptic plasticity in hippocampus.…”
Section: Discussionmentioning
confidence: 99%